Food choice in transition: adolescent autonomy, agency, and the food environment. Issue 10320 (8th January 2022) - Neufeld, Lynnette M; Andrade, Eduardo B; Ballonoff Suleiman, Ahna; Barker, Mary; Beal, Ty; Blum, Lauren S; Demmler, Kathrin M; Dogra, Surabhi; Hardy-Johnson, Polly; Lahiri, Anwesha; Larson, Nicole; Roberto, Christina A; et al.
Summary: Dietary intake during adolescence sets the foundation for a healthy life, but adolescents are diverse in their dietary patterns and in factors that influence food choice. More evidence to understand the key diet-related issues and the meaning and context of food choices for adolescents is needed to increase the potential for impactful actions. The aim of this second Series paper is to elevate the importance given to adolescent dietary intake and food choice, bringing a developmental perspective to inform policy and programmatic actions to improve diets. We describe patterns of dietary intake, then draw on existing literature to map how food choice can be influenced by unique features of adolescent development. Pooled qualitative data is then combined with evidence from the literature to explore ways in which adolescent development can interact with sociocultural context and the food environment to influence food choice. Irrespective of context, adolescents have a lot to say about why they eat what they eat, and insights into factors that might motivate them to change. Adolescents must be active partners in shaping local and global actions that support healthy eating patterns. Efforts to improve food environments and ultimately adolescent food choice should harness widely shared adolescent values beyond nutrition or health.